PENEGAKAN HUKUM TERHADAP PELAKU PELECEHAN SEKSUAL DIBAWAH UMUR (Studi Kasus : Pelecehan Seksual di SMP X ) - Madeleine Lie; Elisa Novianti; Windisen Windisen; Gavinela Clarissa; Ratu Shyfa N.C. (Fakultas Hukum Universitas Tarumanagara, 2021)
Sexual harassment in Indonesia is rife, especially in educational institutions. This sexual harassment itself can be done by anyone, whether teachers, staff or students in the school. Sadly, cases of sexual harassment that occur in educational institutions in Indonesia are rarely investigated by schools or the authorities on the grounds that